The relationship between HIV status and clinical manifestations of urogenital infections in women during pregnancy: a scoping review - Silva, Anderson Lima Cordeiro da; Santos, Gustavo Gonçalves dos; Nascimento, Edson Silva do; Oliveira Júnior, Ronaldo Eustáquio de (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: Maternal and child health are essential to public health, especially during pregnancy, where urogenital infections can affect mothers and fetuses. Sexually transmitted infections (STIs) increase obstetric risks and have complex connections with the human immunodeficiency virus — HIV. In Brazil, pregnant women with HIV are a growing concern, requiring focus and appropriate interventions. Objective: This study aimed to examine the clinical and epidemiological characteristics of urogenital infections in pregnant women with and without HIV and to assess whether there are notable differences between these groups. Methods: A scoping review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses — Extension for Scoping Reviews (PRISMA-ScR) and Joanna Briggs Institute guidelines. Databases such as Medical Literature Analysis and Retrieval System Online (MEDLINE), Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS), and Scientific Electronic Library Online (SciELO) were explored using relevant terms. Inclusion/exclusion criteria selected nine studies for analysis. A Population, Intervention, Comparison, Outcome, and Study Design (PICOS) approach directed the search. Results: Pregnant women with HIV had a high prevalence of STIs, including Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis, and bacterial vaginosis. HIV infection appears to influence the risk and severity of urogenital infections. Pregnancy increases the risk of STIs, regardless of HIV status. Male partners may also influence the presence of STIs in pregnant women, especially those with HIV. Conclusion: This study highlights the association between HIV status and urogenital infections in pregnant women, indicating the need for appropriate screening and care. Prevention and treatment of STIs in pregnant women are essential for maternal and child health, regardless of HIV status. An in-depth understanding of these issues can improve public policies, clinical practices, and preventive interventions that target the overall health of these vulnerable populations.